Test of a causal Human Resource Management-performance linkage model: Evidence from the Greek manufacturing sector - Anastasia Katou (International Journal of Business Science & Applied Management (IJBSAM), 2011)
Although a number of studies have recognized the relationship between Human Resource Management (HRM) policies and organisational performance, the mechanisms through which HRM policies lead to organisational performance remain still unexplored. The purpose of this paper is to investigate the pathways leading from HRM policies to organisational performance by using structural equation modelling. Specifically, this analytical tool has been used to test a research framework that is constituted by a set of causal relationships between organisational and other contingencies, business strategies, HRM policies, HRM outcomes, and organisational performance. Employing data from organisations operating in the Greek manufacturing sector, results indicate that the impact of HRM policies on organisational performance is mediated through the HRM outputs of skills, attitudes and behaviour, and moderated by business strategies, organisational context and other contingencies. Thus, the paper not only supports that HRM policies have a positive impact on organisational performance but also explains the mechanisms through which HRM policies improve organisational performance.
Keywords: 650; HRM policies; business strategies; HRM outputs; mediating model; organisational context; Greek manufacturing